Exam problem

Calculus Level 3

Let a n a_n be the n n th term of an arithmetic progression with the initial term a 1 = 2 a_1 = 2 and with the common difference 5. That is a n = 2 + 5 ( n 1 ) a_n = 2 + 5(n-1) . Evaluate

lim n n ( a n 2 + 3 a n 2 3 ) \large \lim_{n\to\infty} n\left(\sqrt{a_n^2+ 3} - \sqrt{a_n^2- 3}\right)

3 5 \frac 35 0 6 13 \frac 6{13} 1 3 \frac 13

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Mar 25, 2018

L = lim n n ( a n 2 + 3 a n 2 3 ) = lim n n ( a n 2 + 3 a n 2 3 ) × a n 2 + 3 + a n 2 3 a n 2 + 3 + a n 2 3 = lim n 6 n a n 2 + 3 + a n 2 3 Note that a n = 2 + 5 ( n 1 ) = 5 n 3 = lim n 6 n 25 n 2 30 n + 12 + 25 n 2 30 n + 6 Divide up and down by n = lim n 6 25 30 n + 12 n 2 + 25 30 n + 6 n 2 = 6 25 + 25 = 3 5 \begin{aligned} L & = \lim_{n \to \infty} n \left(\sqrt{a_n^2+3}-\sqrt{a_n^2-3}\right) \\ & = \lim_{n \to \infty} n \left(\sqrt{a_n^2+3}-\sqrt{a_n^2-3}\right) \times \frac {\sqrt{a_n^2+3}+\sqrt{a_n^2-3}}{\sqrt{a_n^2+3}+\sqrt{a_n^2-3}} \\ & = \lim_{n \to \infty} \frac {6n}{\sqrt{a_n^2+3}+\sqrt{a_n^2-3}} & \small \color{#3D99F6} \text{Note that }a_n = 2+5(n-1) = 5n-3 \\ & = \lim_{n \to \infty} \frac {6n}{\sqrt{25n^2-30n+12}+\sqrt{25n^2-30n+6}} & \small \color{#3D99F6} \text{Divide up and down by }n \\ & = \lim_{n \to \infty} \frac 6{\sqrt{25-\frac {30}n+\frac {12}{n^2}}+\sqrt{25-\frac {30}n+\frac 6{n^2}}} \\ & = \frac 6{\sqrt {25}+\sqrt{25}} \\ & = \boxed{\dfrac 35} \end{aligned}

Nice manipulation. Did it exactly the same way.

Peter van der Linden - 3 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...